Fostering Creativity in Primary Education: A Literature Review of Creative Pedagogy Strategies, Facilitators, and Barriers - Nurani Fitriyah; Farida Kurniawati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Creativity is increasingly recognized as a core 21st-century competency in global education reforms, particularly in primary education where early creative development is critical. Lin’s Creative Pedagogy framework—integrating creative teaching, teaching for creativity, and creative learning—offers a holistic approach. However, most existing research examines these components in isolation, and systematic reviews focusing on primary education and recent developments remain limited. This study conducted a systematic literature review to explore strategies, facilitators, and barriers related to creative pedagogy in primary education from 2014 to 2024. Following PRISMA guidelines, 25 peer-reviewed empirical studies were selected from Scopus, Taylor Francis, and Google Scholar databases. The analysis identified a range of student-centered pedagogical strategies, including problem-based, project-based, experiential, game-based, art-based, and STEM-based approaches. These methods were found to enhance student engagement, critical thinking, and creativity. Key facilitators of creative pedagogy included supportive school environments, ongoing professional development, and teachers’ self-efficacy. Conversely, common barriers included cultural expectations, high-stakes assessment systems, time constraints, and inflexible classroom structures. This review offers a contemporary synthesis of creative pedagogy in primary education, highlighting both progress and persistent challenges. By mapping recent trends and implementation factors, the study contributes to a deeper understanding of how creativity can be more effectively integrated into early education. The findings offer practical insights for educators, policymakers, and researchers aiming to foster creativity-driven learning environments in primary schools.